Mental Health of Flying Cabin Crews: Depression, Anxiety, and Stress Before and During the COVID-19 Pandemic - Görlich, Yvonne; Stadelmann, Daniel (Frontiers in Psychology, 2020)
Objectives: Initially, we analyzed relations between the challenging working conditions of flight attendants with symptoms of depression, anxiety and stress. As the COVID-19 pandemic plunged airlines into an unprecedented crisis, its impact on the mental health of flying cabin crews became the focus of a second survey. Methods: Flight attendants were surveyed online with DASS-21 in May 2019 (N=105; sample 1) and April 2020 (N=1119; sample 2), complemented with questions about working conditions (in 2019) and existential fears and fear of job loss (in 2020). Results: Sample 1 revealed that symptoms of depression, anxiety and stress highly correlated with the subjective assessment of working conditions, but not with objectifiable parameters. Sample 2 showed significant positive correlations between existential fears and fear of job loss with depression, anxiety and stress. Crew members, grounded in April 2020, showed significantly higher scores in depression and stress, while still flying individuals had more clinically relevant symptoms of anxiety. Mean value comparisons between sample 1 and 2 in DASS-21 revealed a significant increase in symptoms at the time of crisis with effect sizes of d=0.63 for depression, d=0.26 for anxiety and d=0.52 for stress. The incidence of clinically relevant symptoms amongst the respondents increased from 8% to 23% (depression), from 6% to 14% (anxiety) and from 8% to 24% (stress). Conclusion: The COVID-19 pandemic and associated work restrictions coincide with severe impairment of mental health of flying cabin crews, consistent with a mental health protecting function of labour.